Carbon Dioxide Emissions Reductions in New Zealand: A Minimum Disruption Approach - John Creedy; Catherine Sleeman (New Zealand Government, The Treasury, 2004)
Reductions in carbon dioxide emissions can come from (among other things) changes to the structure of final demands, changes in the use of fossil fuels by industry, and changes to the structure of inter-industry transactions. This paper examines the nature of the least disruptive changes, that is the minimum changes to these three components which are consistent with specified overall reductions in carbon dioxide in New Zealand. In examining the minimum changes needed, constraints are imposed on the corresponding changes in GDP growth and aggregate employment.
Keywords: D57; Q40; L70; 330; Carbon Dioxide; Minimum Disruption; Carbon Intensities; New Zealand